Mechanical activation as an innovative approach for the preparation of pozzolan from iron ore tailings - Yao, Geng; Wang, Qiang; Su, Yuewei; Wang, Junxiang; Qiu, Jun; Lyu, Xianjun (Minerals engineering, 2020)
•The pozzolanic activity of iron ore tailings was improved after mechanical activation.•The hydration products of CaO-activated tailings are CSH gel, as well as ettringite crystals in the presence of anhydrite.•It is feasible to use mechanically activated iron ore tailings as Portland cement additive. The harm caused by mine tailings to human society has become increasingly prominent and the utilization of mine tailings has become the focus of research in recent years. The pozzolanic reaction activity of iron ore tailings (IOTs), which is of great significance for the effective treatment of the tailings and their efficient utilization as supplementary cementitious material was investigated in this study. The reactivity of IOTs was characterized by comparing the pozzolanic activity and hydration properties of mechanically activated IOTs obtained by mechanical activation in a vertical planetary mill and amorphous ground granulated blast furnace slag (GGBFS) with the similar specific surface area as IOTs. The results demonstrated that the mechanically activated IOTs exhibited similar hydration properties to GGBFS, but their pozzolanic activity was lower. The major hydration products of the CaO-activated mechanically ground IOTs/GGBFS pastes were both amorphous CSH gel, as well as ettringite crystals in the presence of natural anhydrite, differing only in amounts. The compressive strength of the activated IOTs-based paste sample was lower, but had a long-term strength development trend than GGBFS based past sample. In addition, the elemental compositions of the CSH gel in the activated IOTs-based paste exhibited a lower atomic ratio of Ca/Si than GGBFS based past at the same curing time. The aluminosilicate minerals in activated IOTs have positive effects on the reaction activity, and the pozzolanic activity index (28 d) of the activated IOTs was tested to be qualified for usage as active mixture in cement. This study provides an innovative approach for the utilisation of crystalline IOTs in an environmentally friendly manner.